PERAN GURU FIKIH DALAM MENUMBUHKAN MINAT BERBUSANA MUSLIMAH PESERTA DIDIK DI SMPIT QURRATU A’YUN AL-ISLAMI KABUPATEN MAROS - Nurhidayanti; Mustamin; Raehana, Syarifa; Wahab, Abdul; Martini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the role of Fiqh teachers in fostering students’ interest in wearing Islamic attire at SMPIT Qurratu A’yun Al Islami, Maros Regency. The background of this research is based on the importance of instilling Islamic character values from an early age, one of which is through encouraging students to dress according to Islamic guidelines. This is a descriptive qualitative study using interviews, observation, and documentation as data collection techniques. The main informant in this study was Ustadzah Syamsunarti Iskandar, the Fiqh teacher at the school. The results show that the Fiqh teacher plays a role as an educator, motivator, and role model in encouraging female students to develop an interest in Islamic dress. The strategies used include delivering relevant Fiqh material, applying a personal approach, and setting daily examples. The study concludes that the active role of the Fiqh teacher has a significant influence in building students’ awareness and interest in dressing in accordance with Islamic teachings.